BCG lymphadenitis: a potential complication of immune reconstitution following haematopoietic stem cell transplant. Issue 4 (18th December 2020) - Tsilifis, Christo; Schim van der Loeff, Ina; Williams, Eleri; Owens, Stephen; Powell, Steven; Gennery, Andrew; Slatter, Mary
Abstract : Case report: An MHC class II deficient 2-year-old boy presented with fever and an enlarging left neck mass 100 days post allogeneic haematopoietic stem cell transplant (HSCT). Fever persisted despite treatment with broad-spectrum β-lactam antibiotics. His BCG vaccination site at presentation was quiescent. Ultrasound showed enlarged cervical lymph nodes. An incisional biopsy of the large nodal mass yielded acid-fast bacilli, identified as Mycobacterium bovis by genome sequencing. Treatment with rifampicin, isoniazid and pyridoxine was started. The mass suppurated (figure 1 ), before healing concurrently with T-lymphocyte reconstitution at approximately day 130 post-HSCT. BCG infection can complicate vaccination in patients with severe combined immunodeficiencies (SCID), including MHC II deficiency 1 1 causing a spectrum ranging from simple adenitis to disseminated disease. BCG immune reconstitution inflammatory syndrome, typically presenting as localised adenitis ipsilateral to vaccination site, is well-described after commencing antiretroviral therapy for HIV and is recognised in patients post-HSCT. 22 3 2 33 In this case, T-lymphocyte reconstitution restoring the T-lymphocyte mediated response in a previously BCG-vaccinated child is likely to have precipitated both this presentation and its resolution. Early identification of SCID though newborn screening might prevent vaccine administration to patients at risk of complications. Questions: How is MHC class II deficiency inherited? Autosomal dominant Autosomal recessive X-linked recessive Mitochondrial What role do MHC class II molecules have in the immune response? Costimulation of naïve CD4+ T-helper lymphocytes to prevent anergy Initiation of immunoglobulin class-switch recombination in B-lymphocytes Presentation of antigen to naïve CD4+ T-lymphocytes Presentation of antigen to naïve CD8+ T-lymphocytes Which method has been proposed for newborn screening for SCID in the UK? Absolute lymphocyte count Detection of T-lymphocyte receptor excision circles (TRECs) Tandem mass spectrometry to detect toxic metabolites Immunoassay for CD3 and CD45 Which is the most appropriate treatment for localised BCG disease in immunocompromised children? Rifampicin and isoniazid Surgical resection Surgical resection and instillation of isoniazid Rifampicin, isoniazid, ethambutol and pyrazinamide What common side-effect should patients receiving isoniazid be counselled for? Peripheral neuropathy Increased seizure frequency Acute kidney injury Change in colour of urine Answers can be found on page 2.